Impacts of operating conditions on specific cake resistance in dead-end microfiltration process - Khaliunaa, Natsagdorj; Zhan, Wang; Wang, Xi; Bold, Tungalagtamir (Proceedings of the Mongolian Academy of Sciences, 2023)
In the present work, the fouling behavior and the corresponding specific cake resistance of polyethersulfone microfiltration membrane fouled by using different solutions (bovine serum albumin solution, sodium alginate solution, humic acid and activated sludge suspension) under different operating conditions, transmembrane pressure (TMP), concentration (C), stirred speed (ω) and temperature (T) were systematically investigated. The ensuing results showed that the proposed equation can be used to accurately calculate instantaneous specific cake resistance (α). The average specific cake resistance increased with increasing operating pressure, concentration, and stirred speed, while it decreased with increasing operating temperature. The average specific cake resistance of sodium alginate (SA) was larger and the sequence was SA>HA>BSA>AS.